2013
DOI: 10.1002/stem.1356
|View full text |Cite
|
Sign up to set email alerts
|

Shockwaves Induce Osteogenic Differentiation of Human Mesenchymal Stem Cells Through ATP Release and Activation of P2X7 Receptors

Abstract: Shockwave fractures treatment promotes bone healing of nonunion fractures. In this study, we investigated whether this effect could be due to adenosine 5’-triphosphate (ATP) release-induced differentiation of human mesenchymal stem cells (hMSCs) into osteoprogenitor cells. Cultured bone marrow-derived hMSCs were subjected to shockwave treatment and ATP release was assessed. Osteogenic differentiation and mineralization of hMSCs were evaluated by examining alkaline phosphatase activity, osteocalcin production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
112
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 60 publications
10
112
0
Order By: Relevance
“…Mechanical stimulation has been shown to mediate the release of cellular ATP of various cells such as astrocytes, osteoblasts, chondrocytes, and epithelial cells (46 -49). Studies by Sun et al (23) and Yu et al (22) support our finding that ESWT at our chosen settings releases ATP without negatively affecting cell viability as they showed that subjection of human mesenchymal stem cells to Ͻ200 shock wave pulses at 0.18 mJ/mm 2 resulted in Ͼ95% viability directly or 24 h after ESWT.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Mechanical stimulation has been shown to mediate the release of cellular ATP of various cells such as astrocytes, osteoblasts, chondrocytes, and epithelial cells (46 -49). Studies by Sun et al (23) and Yu et al (22) support our finding that ESWT at our chosen settings releases ATP without negatively affecting cell viability as they showed that subjection of human mesenchymal stem cells to Ͻ200 shock wave pulses at 0.18 mJ/mm 2 resulted in Ͼ95% viability directly or 24 h after ESWT.…”
Section: Discussionsupporting
confidence: 82%
“…We found that the released ATP activated P2 receptors and increased Erk1/2 and p38 MAPK signaling via mechanisms similar to those reported in osteoblasts, mesenchymal stem cells, and T cells (20,(22)(23)(24). In addition to Erk1/2 and p38 MAPK, the downstream signaling mechanisms triggered by shock wave-induced P2 receptor activation may also involve additional signaling intermediates such as Ras and hypoxiainducible factor 1a transactivation (20,23).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, they report that these orthopaedic disease processes can be attenuated/modulated by targeting adenosine triphosphate (ATP) hydrolysis and SMAD1/5/8 phosphorylation at the burn site using apyrase [19]. Interestingly, it has been reported that focused extracorporeal shockwave therapy (ESWT; low-density shockwaves administered orders of magnitude below blast overpressure conditions used in the study) has been shown to induce osteogenic differentiation of marrow-derived mesenchymal stem cells through ATP release and downstream transcriptional signaling events resulting in activation of P2X7 receptors [28]. Consistent with the finding of Peterson et al, removal of ATP using apyrase inhibited ESWT-induced osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 98%